Amargas mistidas. O desalento africano em Desesperança no chão de medo e dor de Tony Tcheka - Łukaszyk, Ewa A. (Studia Romanica Posnaniensia, 2019)
The essay focuses on selected poems from the volume Desesperança no chão de medo e dor published in 2015. Tony Tcheka offers a bitter comment on the reality of his native Guinea-Bissau that, for analytical sake, is confronted with other voices of the country. The topics discussed are: the crisis of collective identity, as well as such values as freedom and solidarity; the deficient status of Kriol as a supposed “national” language; sexuality and gender issues, such as promiscuity and insufficiency of male role models; the status of traditional beliefs and tribal identifications.